2012
DOI: 10.1007/s12253-012-9542-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of SOX7 is Correlated with Poor Prognosis in Lung Adenocarcinoma Patients

Abstract: Lung adenocarcinoma is the most frequently histologic subtype and the most histologically heterogeneous form of lung cancer. De-regulation of Wnt/β-catenin signaling pathway is implicated in lung carcinogenesis. SOX7, as a member of high mobility group (HMG) transcription factor family, plays a role in the modulation of the Wnt/β-catenin signaling pathway. However, the expression pattern and clinicopathological significance of SOX7 in patients with lung adenocarcinoma is still unclear. To address this problem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 20 publications
3
42
0
1
Order By: Relevance
“…Hayano T et al found SOX7 was a novel tumor suppressor gene which was silenced in lung cancer [21]. Li B et al also reported that decreased SOX7 level was correlated with poor prognosis of lung adenocarcinoma [22]. Zhou X et al found that SOX7 was involved in aspirin-mediated growth inhibition of colorectal cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hayano T et al found SOX7 was a novel tumor suppressor gene which was silenced in lung cancer [21]. Li B et al also reported that decreased SOX7 level was correlated with poor prognosis of lung adenocarcinoma [22]. Zhou X et al found that SOX7 was involved in aspirin-mediated growth inhibition of colorectal cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…PITX2 is a downstream effector of Wnt/β-catenin signaling. Deregulation of Wnt signaling is strongly associated with LAC progression [18,19]. More recently, PITX2 can activate the proliferation of cancer cells by inducing the expression of canonical Wnt ligand genes, and in turn activates the signaling pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SOX7 may have potential usage as an independent prognostic marker in prostate and lung cancers as well as MDS patients [11,12,29]. Several lines of evidence indicate SOX7 as a negative regulator of the Wnt/β-catenin signaling pathway [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SOX7 may be involved in aspirin-mediated growth inhibition of COX2 colorectal cancer cells, in which aspirin may up-regulate the expression of SOX7 by activating the MAPK [17]. There are also reports indicating that the decreased expression of SOX7 is an important feature of lung adenocarcinoma [12]. Based on whole genome analysis to measure the expression of SOX7 on a series of non-small cell lung cancers (NSCLC), investigators have shown that SOX7 is a novel tumor suppressor gene silenced in the majority of NSCLC [19].…”
Section: Introductionmentioning
confidence: 99%